Recent Advances in Plant Fertilizers Technology - Alkhatib, Laila; Al-Shiyab , Safwan; Sawan, Jamal (Jordan Journal of Agricultural Sciences, 2025)
Fertilizer is a crucial subject as it affects plant growth besides the surrounding soil environment and the environment at large. Deep water percolation usually drains excess soluble fertilizers to the underground water reservoirs. Finding the most proper fertilizer that can gradually and efficiently feed plants' requirement from nutrients and keep good interaction with soil, microorganisms and the surrounding environment can be promising. Conventional fertilizers have been in use for decades. The development of nanoparticulate fertilizers is becoming a trend in the industry. Plants and soil interact positively or negatively with nanoparticles depending on nanoparticle type, concentration, and level. Nano-size particles are premium fertilizers when taken in precise levels, sizes, and types, and given to the most proper plants; they can provide great advantages to the plants and surrounding environment. Microsize particle fertilizer can be promising, but the topic needs further studies.